Long-term impact of activation circuit-based ventricular tachycardia ablation on ventricular arrhythmia burden. (19th May 2022) - Freire Barbas De Albuquerque, F; Portugal, G; Silva Cunha, P; Valente, B; Lousinha, A; Delgado, AS; Paulo, M; Rosa, T; Bras, M; Cruz Ferreira, R; Oliveira, M
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Ventricular arrhythmias (VA) are a major cause of morbidity and mortality in heart failure patients. Ventricular tachycardia (VT) ablation is an established treatment for the reduction of recurrent implantable cardioverter-defibrillator (ICD) therapies in this population. In patients with substrate-related VT, mapping of the entire tachycardia circuit, when feasible, may allow for more accurate targeting of the clinical VT. Purpose: To assess the long-term impact of catheter ablation based on activation mapping of substrate-related VT on VA burden. Methods: Consecutive patients submitted to VT ablation between January 2013 and October 2021 were included. A comprehensive review of clinical records and device monitoring was performed to assess VA burden, defined as all ICD therapies and clinically documented VTs, before and after ablation. The primary outcome was reduction in the overall burden of VA after ablation. The impact of ablation on VA burden was assessed by fixed-effects Poisson regression; comparison at fixed time intervals was performed with a paired-sample Wilcoxon signed-rank test (STATA 12, JASP). Results: A total of 134 VT ablation procedures were performed during the study period. Of these, there were 21 procedures where complete mapping of the VT activation circuit was achieved, corresponding to 18 patients. Mean age was 56.7 years, 88% male sex, mean left ventricular ejection fraction 39 ± 13%, BNP 540 ± 627 pg/mL. Etiology was ischemic in 44%, non-ischemic dilated cardiomyopathy in 39%, arrhythmogenic right ventricular dysplasia in 11% and hypertrophic cardiomyopathy in 6%. Mechanical support was in situ in 3 patients (two with temporary VA ECMO and one with LVAD as destination therapy); all but one patient had an ICD. Procedural duration was 209 ± 61 minutes. One patient developed complete AV block; no other peri-procedural complications were observed. During follow-up two patients died due to heart failure, one patient died from refractory cardiogenic shock with refractory incessant VT and one patient underwent orthotopic heart transplant. The mean follow-up time after ablation was 2.2 ± 1.9 years. A significant reduction in VA burden was observed (Figure 1) at 3 months (92.5% reduction, p=0.002) and 6 months after ablation (83.3% reduction, p=0.041). After fixed-effects Poisson regression, there was an estimated long-term reduction of 75% (CI 12-93%, p=0.031) of VA burden after VT circuit ablation. Conclusion: Targeted circuit ablation is feasible in a subset of patients referred to VT ablation and leads to a significant sustained decrease in VA burden and device therapies.